Myringosclerosis as a predictor of the requirement for a permanent pacemaker in patients with drug-related atrioventricular block - Cosgun, Muharrem Said; Hamur, Hikmet; Degirmenci, Husnu; Coskun, Resit; Karayumak, Mustafa Rauf; Karabiyik, Ugur; Salcan, Ismail (Biomedical papers, 2022)
Aims. Drug-related atrioventricular block (DR-AVB) may develop in patients with underlying latent degenerative conduction disorders, especially with antiarrhythmics and antihypertensives. Although, according to the current guidelines, reversal is achieved with cessation of the inducing agent, this is not the case for nearly half of the patients. The pathophysiological processes of DR-AVB and myringosclerosis include systemic inflammation and degeneration. This study investigated the role of myringosclerosis in predicting irreversible high-grade DR-AVB despite drug cessation. Methods. This observational, non-randomized, prospective study involved 152 patients with high-grade DR-AVB, 72 of whom had reversible DR-AVB and 80 had irreversible DR-AVB and required permanent pacemakers. The patients' demographic, clinical, echocardiographic, and laboratory characteristics were recorded. Otoscopic tympanic membrane examinations for myringosclerosis were performed. Results. There were no major differences in demographic, echocardiographic or laboratory characteristics between the two groups or previous medications. The median monitoring time with a temporary pacemaker was significantly longer in the irreversible than in the reversible group (5 [4-7] days vs. 2 [1-5] days; P<0.001). The incidence of myringosclerosis was significantly higher in the irreversible than in the reversible group (61.3% vs. 22.2%; P=0.001). Multivariate logistic regression analysis showed that myringosclerosis was an independent predictor of irreversible DR-AVB (odds ratio: 1.703, 95% confidence interval: 1.194-3.058; P=0.01). Conclusion. Myringosclerosis is a readily available, inexpensive, and non-invasive assessment and is a marker of inflammation and degeneration that can predict irreversible DR-AVB.
Keywords: atrioventricular block; myringosclerosis; pacemaker; tympanosclerosis